2004
DOI: 10.1158/1078-0432.ccr-03-0588
|View full text |Cite
|
Sign up to set email alerts
|

trans- 3,4,5′-Trihydroxystibene Inhibits Hypoxia-Inducible Factor 1α and Vascular Endothelial Growth Factor Expression in Human Ovarian Cancer Cells

Abstract: ABSTRACTtrans-3,4,5-Trihydroxystibene (resveratrol) is a natural product commonly found in the human diet and has been shown recently to have anticancer effects on various human cancer cells. However, the molecular basis for its anticancer action remains to be elucidated. In this study, we investigated the effect of resveratrol on hypoxia-inducible factor 1␣ (HIF-1␣) and vascular endothelial growth factor (VEGF) expression in human ovarian cancer cells A2780/CP70 and OVCAR-3. We found that although resveratrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
134
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 41 publications
13
134
1
1
Order By: Relevance
“…From the literature β-catenin is found to be a critical mediator during development and angiogenesis [24], which is phosphorylated in a cytosolic multiprotein complex containing adenomatous polyposis coli protein (APC), Axin and GSK-3β [24][25][26][27]. When phosphorylation of β-catenin is blocked, this allows β-catenin to accumulate and translocate into nucleus, where it forms a complex with T-cell transcription factors/lymphoid-enhancer binding factor (TCF/LEF) family of transcription factors and is able to activate or repress several important target genes, such as c-Myc, cyclin D1, fibronectin, VEGF, Bcl-2 and survivin [28][29][30][31]. VEGF expression was found to be increased in HC (1.15 fold), HCR (1.86 fold), HCS (1.3 fold), HCRS (1.5 fold) when compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature β-catenin is found to be a critical mediator during development and angiogenesis [24], which is phosphorylated in a cytosolic multiprotein complex containing adenomatous polyposis coli protein (APC), Axin and GSK-3β [24][25][26][27]. When phosphorylation of β-catenin is blocked, this allows β-catenin to accumulate and translocate into nucleus, where it forms a complex with T-cell transcription factors/lymphoid-enhancer binding factor (TCF/LEF) family of transcription factors and is able to activate or repress several important target genes, such as c-Myc, cyclin D1, fibronectin, VEGF, Bcl-2 and survivin [28][29][30][31]. VEGF expression was found to be increased in HC (1.15 fold), HCR (1.86 fold), HCS (1.3 fold), HCRS (1.5 fold) when compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is conceivable that chrysin may also inhibit HIF-1a via AKT signaling. It was reported that flavonoids or related compounds, such as apigenin (28,46), resveratrol (47), and (À)-epigallocatechin-3-gallate (48), inhibited expression of HIF-1a through multiple pathways, including protein synthesis and protein degradation. Consistent with previous reports, we show here that chrysin is also multifunctioning in HIF-1a pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Further, alterations in the angiogenic characteristics of ovarian surface epithelium may play an important role in the etiology of ovarian cancer (Schumacher et al, 2007). Human ovarian cancer progression and angiogenesis were reduced by resveratrol through suppression of hypoxia-inducible factor 1α (HIF-1α) and vascular endothelial growth factor (VEGF) as observed (Cao et al, 2004). Thus, the potential array of therapeutic targets for this remarkable natural compound implicates the novel rationale for resveratrol as an extremely attractive candidate in the treatment of ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%